Operations management strategies and its impact on customer delight / exploratory study in factory (Al kanz) - Jayan, Reem Abdulkareem; Shawkat, Tamara Nidhal (Journal of Economics and Administrative Sciences, 2020)
Purpose – measure the relationship between operation management strategies as an independent variable on the customer's delight as an approved variable.Design/methodology/approach – The research sample vocabulary included sales representatives and customers of the researched markets at a rate of (100%). The recovery rate is (95) Customers and (95) delegates for the products for the factory in neighbourhood (Banooks and Karrada ) regions were randomly chosen from an open community in these two residential areas. Statistical methods were used (arithmetic media, standard deviations, t-test,  correlation coefficient (Horst), simple regression analysis).Findings – The people in charge of the factory management need to pay attention to the continuous promotion and updates that adopt the availability of the two elements of excitement and suspense in order to achieve the expectation and surprise of the customer that increases his joy, in order to achieve increased customer demand for their product.Practical implications – Defining and improving operations management strategies to enhance customer delight, and achieve maximum levels of satisfaction, which is customer delight.Originality/value – The research is a new addition to studies in linking the two variables, as the research came to increase the strength of the private sector, encourage production, the independence of the country, and control of the local markets.